Drug safety among institutionalized elderly people: potential interactions - Maria Lígia Silva Nunes Cavalcante; Renata Kelly Lopes de Alcântara; Isabelly Costa Lima de Oliveira; Samia Freitas Aires; Ana Lívia Araújo Girão; Rhanna Emanuela Fontenele Lima de Carvalho (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to identify the drug interactions among institutionalized elderly. Method: retrospective and documentary study with a quantitative approach developed in two Long Stay Institutions for Elderly, located in northeastern Brazil. Drug interactions were identified by using Drug-Reax® software from the Micromedex database, and they were classified by severity, start time, and documentation. Result: in the 286 analyzed prescriptions, 136 drug interactions were detected in both institutions, most of them classified as severe. The average number of drugs prescribed by the elderly was 4.5. In the analysis of Pearson's correlation, the number of drug interactions showed a statistically significant correlation with the time of institutionalization and with the amount of drugs administered on the day. Conclusion and implications for practice: the high consumption of drugs and serious drug interactions detected with significant clinical repercussions was evidenced in the study. Knowledge of these interactions is essential for the establishment of preventive safety measures in pharmacotherapy.